Treatment and Follow-up of Non-stress Adrenal Insufficiency - Fuat Buğrul; Nurhan Özcan Murat (JCRPE, 2025)
Adrenal insufficiency (AI) is defined as the inability of the adrenal cortex to produce adequate amounts of glucocorticoids and/or mineralocorticoids. As these hormones have important roles in water-salt balance and energy homeostasis, AI is a serious and potentially life-threatening condition. Glucocorticoid replacement therapy is vital in all cases of AI. In children with primary AI (PAI), it is recommended to start glucocorticoid replacement therapy with three or four doses of hydrocortisone and adjust according to individual need. Long-acting glucocorticoids such as prednisolone and dexamethasone are not recommended in children with AI. Mineralocorticoid and salt replacement therapy is also necessary in PAI with aldosterone deficiency. In childhood, it is recommended that patients are monitored at least every three to four months with clinical evaluation including weight gain, growth rate, blood pressure and general well-being of the patient. To prevent adrenal crisis in patients with PAI, glucocorticoid dose adjustment is recommended to patients and/or their families according to the magnitude and severity of the stress situation. This education should include recognition of conditions leading to adrenal crisis, signs of adrenal crisis and how to respond to an impending adrenal crisis. With long-term use of glucocorticoids, the lowest possible dose should be maintained to control the disease to avoid possible side effects. Here, members of the ‘Adrenal Working Group' of ‘The Turkish Society for Pediatric Endocrinology and Diabetes' present an evidence-based review with good practice points and recommendations for the diagnosis and follow-up of non-stress AI.